Design and Implementation of a Blood pH Monitoring System Using Arduino for Patients with Renal Failure: Towards Smart and Accurate Healthcare - Aliwi Al-Maliki, Alialakbar Jasim Mohsin; Mahmood, Haider Majid Abd Al Adil; Aldulaimi, Abdullah Falih Shalaan; Alameer, Ali Mohammed Fawzi Abd (American Journal of Botany and Bioengineering, 2025)
The rapid response of emergency medical services plays a critical role in saving lives during emergencies. This paper presents the design and development of a GPS and GSM-based ambulance tracking system integrated with real-time health monitoring of patients. The system uses a GPS module to continuously track the ambulance’s location and a GSM module to transmit location and patient data to a centralized control unit. Additionally, vital signs such as heart rate and body temperature are monitored using biomedical sensors and transmitted wirelessly to ensure timely medical assessment. The proposed system aims to reduce emergency response times, provide real-time data for medical preparedness, and improve overall patient outcomes. The design is low-cost, scalable, and suitable for deployment in both urban and rural settings.